2017
DOI: 10.1038/nenergy.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Efficient ambient-air-stable solar cells with 2D–3D heterostructured butylammonium-caesium-formamidinium lead halide perovskites

Abstract: Three-dimensional (3D) organic-inorganic perovskite solar cells have undergone a meteoric rise in cell efficiency to > 22%. However, the perovskite absorber layer is prone to degradation in water, oxygen and UV light. Two-dimensional (2D) Ruddlesden−Popper layered perovskites have exhibited promising environmental stability, but perform less well in solar cells, possibly due to the inhibition of out-of-plane charge transport by the insulating spacer cations. Alternatively, moving away from methylammonium, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
1,249
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,294 publications
(1,287 citation statements)
references
References 51 publications
34
1,249
3
1
Order By: Relevance
“…[24] In a similar report, a 3D-2D (MAPbI 3 -PEA 2 PbI 4 ) graded perovskite film resulted in an overall PCE of 19.89%. [26][27][28][29] Very recently, Lee et al incorporation of PEA 2 PbI 4 into the precursor solution of FAPbI 3 . [26][27][28][29] Very recently, Lee et al incorporation of PEA 2 PbI 4 into the precursor solution of FAPbI 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[24] In a similar report, a 3D-2D (MAPbI 3 -PEA 2 PbI 4 ) graded perovskite film resulted in an overall PCE of 19.89%. [26][27][28][29] Very recently, Lee et al incorporation of PEA 2 PbI 4 into the precursor solution of FAPbI 3 . [26][27][28][29] Very recently, Lee et al incorporation of PEA 2 PbI 4 into the precursor solution of FAPbI 3 .…”
Section: Introductionmentioning
confidence: 99%
“…

application-oriented research like process engineering and upscaling is observed. [15][16][17][18][19][20] Further advances in stability are based on the charge extracting materials and their interfaces with the perovskite absorber layers. Recently, power conversion efficiencies (PCEs) close to 24% were demonstrated for perovskite PV, exceeding the PCEs of established thinfilm technologies.

…”
mentioning
confidence: 99%
“…The generic molecular formula of 2D RP lead iodide perovskites can be written as (L) 2 A n−1 Pb n I 3n+1 where L + is alkylammonium cation-typically phenylethylamine (C 8 H 11 N, PEA) and butylamine (n-BA), A + is monovalent organic cations such as CH 3 NH 3 + , and the n value is the number of Pb−I octahedral layers between adjacent spacers. [21][22][23][24][25][26][27] 2D Ruddlesden-Popper (RP) perovskite solar cells have manifested superior operation durability yet inferior charge transport compared to their 3D counterparts. [19] Besides, the bandgap (E g ) of 2D perovskites increases with narrowing the thickness of the quantum wells (i.e., decreasing the n value), which is incompatible with making use of the full solar spectrum.…”
mentioning
confidence: 99%